Farewell to the first Editor-in-Chief and some thoughts from the new Editors-in-Chief - Reuchamps, Min; Russo, Luana (Politics of the Low Countries, 2022)
In this editorial, the new Editors-in-Chief, Min Reuchamps and Luana Russo, look back on the work of outgoing Editor-in Chief, Nicolas Bouteca, for Politics of the Low Countries.